PENGARUH PENGETAHUAN WANITA USIA SUBUR TERHADAP PERILAKU DALAM MELAKUKAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) - Hasnita, Yenda; Meiriza, Wira (Jurnal Sains, Teknologi dan Kesehatan, 2023)
Cancer cases are the second leading cause of death in the world, with a total of 9.6 million deaths per year, including 65,858 cases of breast cancer. It is necessary to increase public awareness of the risk of breast cancer by carrying out early detection with the BSE method (Breast Self-Examination). This research is an analytic survey study with a cross-sectional design that aims to determine the relationship between knowledge and BSE behavior in women of childbearing age (WUS). The population in this study were all WUS in Pustu Koto Tuo, Agam Regency; the sample in this study was 50 respondents using a simple random sampling technique. The data analysis technique used was univariate and bivariate with the chi-square test. In univariate analysis, there were 20 respondents with low knowledge (40%), and 19 respondents (61.3%) had never done BSE. The Chi-squared statistical test showed that there was a significant relationship between knowledge about breast self-examination (BSE) and BSE behavior, with a p value of 0.000. It is hoped that health workers can provide counseling, especially about continuous breast self-examination, to the public, especially WUS, so that they can change behavior or raise public awareness of the importance of early detection of breast cancer.